2018
DOI: 10.1021/acsnano.8b02371
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Low-Power Smart Electronic Nose System Based on Three-Dimensional Tin Oxide Nanotube Arrays

Abstract: In this work, we present a high-performance smart electronic nose (E-nose) system consisting of a multiplexed tin oxide (SnO) nanotube sensor array, read-out circuit, wireless data transmission unit, mobile phone receiver, and data processing application (App). Using the designed nanotube sensor device structure in conjunction with multiple electrode materials, high-sensitivity gas detection and discrimination have been achieved at room temperature, enabling a 1000 times reduction of the sensor's power consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 108 publications
(64 citation statements)
references
References 49 publications
0
64
0
Order By: Relevance
“…This concept is anticipated to serve as a model for future IAQ-monitoring devices. In other research, Chen et al developed a high-performance smart E-nose system comprising a multiplexed tin oxide (SnO 2 ) nanotube sensor array, a read-out electronic circuit, a mobile phone receiver, a wireless data transmission unit, and a data processing application [181]. Compared with conventional devices, this nanotube sensor exhibited higher sensitivity gas detection and discrimination at room temperature, owing to the use of nanotube sensors possessing a large surface area for interaction with gas molecules.…”
Section: Internet Of Thing (Iot)-based Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…This concept is anticipated to serve as a model for future IAQ-monitoring devices. In other research, Chen et al developed a high-performance smart E-nose system comprising a multiplexed tin oxide (SnO 2 ) nanotube sensor array, a read-out electronic circuit, a mobile phone receiver, a wireless data transmission unit, and a data processing application [181]. Compared with conventional devices, this nanotube sensor exhibited higher sensitivity gas detection and discrimination at room temperature, owing to the use of nanotube sensors possessing a large surface area for interaction with gas molecules.…”
Section: Internet Of Thing (Iot)-based Systemsmentioning
confidence: 99%
“…Illustration of the proposed electronics nose (E-nose) system architecture (A); the proposed E-nose application in future smart buildings (B); primitive concept design of Smart-Air (C); and a smart ventilation system for optimizing indoor air quality (IAQ) Levels in buildings (D). Reproduced with permission from[180,181,183,184].…”
mentioning
confidence: 99%
“…On the other hand, the system demonstrated in this work is operated in a low‐power mode, and thus the power consumption on interconnects is nearly negligible. Also, sensors with higher sensitivity can be realized with strategies such as nanoengineering by applying 3D porous templates or surface decoration with noble metal nanoparticles . Recent studies also demonstrate the strategies to achieve flexible solar cells (e.g., perovskite solar cells) in printable manners with novel device structures and combination of different printing techniques, and thus a fully printable and wearable self‐powered fabricated on flexible substrate is also promising.…”
mentioning
confidence: 98%
“…SnO 2 as a n‐type semiconductor, is one of the most commonly used material for gas sensing mainly due to its low cost, stability, and repeatability . While metal oxide sensors normally require high operation temperature (over 200 °C) to achieve high sensitivity and fast recovery, recent studies demonstrated the SnO 2 has the capability for volatile organic compounds detection under room temperature, which eliminate the integration of heaters and thermal isolation units . Especially for portable and wearable electronics, room temperature operational sensors are highly desirable for device miniaturization and long cruising time without extra power consumption for heaters .…”
mentioning
confidence: 99%
See 1 more Smart Citation